Over a million students use our free study notes to help them with their homework
Equation 1) x2 + y2 = 25 Equation 2) y - 3x = 13 First you need to substitute a variable so there is only one unknown in the equation: 2) y = 13 + 3x Substituting this into equation ...
So first you need to multiply out the brackets so you can simplify the equation. Remember the acronym FOIL: First, Outer, Inner, Last.10w^2 + 35w - 12w - 42And then you need to simplify10w^2 +...
First we should draw what the question tells us.Draws circle with square inside itWe want to find out some extra information about the circle based on what we have been told.How can w...
First you must convert the diameter into cm from mm:19/10 = 1.9cmThen you must find the radius of the ring:radius = diameter/2 = 1.9/2 = 0.95 cmThen you can calculate the area:area = 2πr2 = 2 x...
First, we simply label the two equations as 'Equation 1' and 'Equation 2' respectively. So we have: Equation 1: 2x + y = 18and Equation 2: x - y = 6. In simultaneous equations, there are two variables: x ...
←
467
468
469
470
471
→
Internet Safety
Payment Security
Cyber
Essentials